Drug metabolism and clearance system in tumor cells of patients with multiple myeloma - Hassen, Wafa; Seckinger, Anja; Hose, Dirk (OncoTarget, 2015)
Oncotarget | https://doi.org/10.18632/oncotarget.3237 Wafa Hassen, Alboukadel Kassambara, Thierry Reme, Surinder Sahota, Anja Seckinger, Laure Vincent, Guillaume Cartron, Jérôme Moreaux, Dirk Hose, Bernard Klein